Heterotic global anomalies and torsion Witten index - Kazuya Yonekura (Journal of High Energy Physics, 2022)
Abstract We study the structure of anomalies in general heterotic string theories by considering general 2-dimensional N $$ \mathcal{N} $$ = (0, 1) supersymmetric quantum field theories (SQFTs), without assuming conformal invariance nor the correct central charges. First we generalize the precise notion of the B-field introduced by Witten. Then we express the target space anomalies by invariants of SQFTs. Perturbative anomalies correspond to the Witten index of some class of SQFTs, while global anomalies correspond to a torsion version of the Witten index. The torsion index gives some of the invariants of SQFTs suggested by topological modular forms, and is expected to be zero for the cases that are relevant to actual heterotic string theories.